Transgression, Stylistic Variation and Narrative Discourse in the Twentieth Century Novel. - Visoi, Marie-Anne (Cambridge Scholars Publishing, 2014)
This book offers a valuable contribution to the practice of literary criticism and cultural studies by seeking to explore ""transgression"" as a literary theme. Based on the analyses of six representative twentieth century novels, it deals with the fictional representation of various transgressive acts, from murder and incest to forbidden love affairs and adultery. A detailed consideration of major reader-response theories establishes a useful context for the textual analyses, as the readers ar ...